The waste management by Grade VIII students through the waste bank at MTs Negeri 6 Sleman - Hukma I Royyan; Saliman Saliman (E3S Web of Conferences)
This study aims to investigate: the implementation of the Waste Bank Program, the constraints in the implementation of the Waste Bank, and the waste management by Grade VIII students through the Waste Bank Program at Madrasah Tsanawiyah Negeri 6 Sleman. This was a study using the quantitative approach. The research population comprised all students of Grade VIII of MTs Negeri 6 Sleman with a total of 155 students. The data were collected using documentation and a questionnaire. The instrument validity was assessed by the product moment correlation and the reliability by Cronbach’s Alpha. The data were analyzed using the descriptive analysis technique. The research was carried out within three months at MTs Negeri 6 Sleman. The results of the study are as follows. The implementation of the Waste Bank Program at in MTs Negeri 6 Sleman is in the moderate category. The constraints in the implementation of the Waste Bank at the school are by is in the low category, The waste management by Grade VIII students through the Waste Bank Program at the school in the moderate category.